Could Congenital Insensitivity to Pain with Anhidrosis Be Misdiagnosed as Papillon–Lefèvre Syndrome? - Mostafa, Mostafa Ibrahim; Abouzaid, Maha Rashed; Thomas, Manal Micheal; El-Kamah, Ghada Yousef (Journal of Pediatric Genetics, 2017)
Papillon–Lefèvre syndrome (PLS) is a rare autosomal recessive disorder characterized by early loss of teeth with hyperkeratosis of the palms and soles. Congenital insensitivity to pain with anhidrosis (CIPA) is a disorder of decreased pain sensation, decreased sweating, recurrent infections, and fever. Here, we report a 5-year-old girl born to consanguineous parents with a family history of a similarly affected sibling. The girl presented with early loss of teeth and palmoplantar hyperkeratosis, hence, provisionally diagnosed as PLS. Further clinical examination and detailed history taking shifted the diagnosis to CIPA. CIPA could be misdiagnosed as PLS. Congenital insensitivity to pain with anhidrosis, although rare, should be considered in the differential diagnosis of PLS.
Keywords: early loss of teeth; congenital insensitivity to pain with anhidrosis; Papillon–Lefèvre syndrome